Host range and host choice of Cuscuta species in Hungary - Barath, Kornel; Csiky, Janos (Acta Botanica Croatica, 2012)
Extensive field studies were carried out in Hungary to get a picture of the hostrange and host choice of the Cuscuta species under natural conditions. We examined both parasitised and unparasitised plant species and found some aspects in which they are different. Compiling the host spectra of the various Cuscuta species based on herbaria, literature and our own observations, we can say that dodders infest at least 26% of the vascular flora of the country. In our study, the Hungarian Cuscuta species parasitised allplants that had a coverage of more than 25% in the sampling sites.We prepared a list of themost frequent host species for the parasites and revealed the importance of exclusive hosts. The results suggest that the habitat differences of the Cuscuta species can be responsible for the different host ranges. Furthermore, it was found that the reason why dodders parasitise plants from various life-forms in different proportions is not (only) the active host choice, but the characteristic features of the habitats.